Teacher Education and Advanced Training in German Settlements of the Taurida Governorate - Ekaterina Kostyleva (Voprosy obrazovaniya / Educational Studies Moscow, 2018)
Archival materials and contemporary studies are used to identify the specific features of teacher education and advanced training in German colonial schools in the Taurida Governorate. The paper investigates into the conditions under which German colonists’ educational institutions evolved, comparing the data on changes in the number of German primary schools and central vocational schools in the Taurida Governorate. It also describes the specific aspects of teaching organization and education content in central vocational schools as educational institutions of advanced type designed to train teachers for German primary schools. Such forms of advanced training for German teachers as temporary teacher education courses and pedagogical conferences are presented.